Side effects of drugs annual. - Aronson, J. K. (Elsevier Science, 1997)
The Side Effects of Drugs Annual has been published each year since 1977. It is designed to provide a critical and up-to-date account of new information related to adverse drug reactions and interactions from the clinician's point of view. Under the supervision of the series editors, an international team of expert authors have gathered together the latest information on adverse drug effects from the international literature. In addition to describing new reports of adverse drug effects, the authors have subjected those reports to critical analysis, setting them into context in terms of clinical relevance and importance, and cross-referring to previous reports where necessary. New adverse effects are reported and evaluated and previously reported adverse effects are re-evaluated in the light of the most recent information. A special feature is the reviews, in which selected adverse effects are discussed in depth. The use of the book is enhanced by two separate indexes, allowing the reader to enter the text by drug name, adverse effect name, or drug interaction. The Annual can be used independently or as a supplement to the standard encyclopaedic work in this field, Meyler's Side Effects of Drugs, of which, the Fourteenth Edition was published in December 2000.